Wiara narodu i religijność w czasach zarazy – o przekształceniach pobożności Polaków - Klimski, Wojciech (Humaniora. Czasopismo Internetowe, 2023)
The subject of the article is the transformation of Poles’ religiousness. They were analysed along two dimensions: nationwide religiousness and the religious dimension of the COVID-19 pandemic. These are two spheres that (in Polish conditions) have a particular chance to activate religiousness. Catholicism is firmly rooted in the nation’s faith, and the plague was the threat that has so far driven individuals towards religion. Transformations in these two spheres are strong indicators of transformations in piety. The research method used is analysing existing research (desk research). The inference carried out showed that Catholicism is fading in these two dimensions. Among the reasons cited for this process, the article points to Poland’s developing social and cultural pluralism, and clergy sex scandals, among others.